tingkat pendapatan usahatani kubis yang di terima oleh para petani Di Rurukan Kecamatan Tomohon Timur. - Ansyu N Dinding (COCOS, 2012)
Ansyu N. Dinding Income Level Cbbage Farming in East Village Tomohon Rurukan District. Under the guidance of J.N.K. Dumais ( Chairman ), Melissa L.G. Tarore ( Member 1 ) and Celcius Talumingan ( Member 2 ). Prombelm in adpted in this study is how much the level of farming income that is received by cabbage farmer and large exspenses in a single growing season. This study aims to determine the level of farmer income as cabbage and benefit information to farmer in regulating the production cost terms of the proper division of time and work hours in order to increase farmer income and with satisfactory result. This study took placein the month of March-May 2012 in the village of East Tomohon Rurukan district. The method used is Simple Random Sampling. The number of samples used in this stady ware as many as 21 landowners cabbage f. Anayisis of the data used in this study is a descriptive analysis Return to Cost Ratio analysis formula to determine the level of success of farmer. The result suggest showed majority of respondens in the village large farmer Rurukan Eastern District Tomohon 40-67 years old have the educational level of elementary through high scool by the number of dependens 1-3 people. The result suggest that the analysis of farmer income cabbage indicate Return Cost Ratio analysis of the value of 6,78 is thus guined acceptance in a single growing season Rp.23.604.000 with a total Cost that is issued in a single growing season Rp. 3.480.118,84 the total revenue is Rp. 20.123.881,16 Existing production and price policies, to assess the level of success in the use of farmer cabbage Return Cost Ratio analysis that gives value and meaning as Rp.6,78 cabbage farming is profitable for the try.